Micro-Assembly of a Vascular-Like Micro-Channel with Railed Micro-Robot Team-Coordinated Manipulation. (31st July 2014) - Wang, Huaping; Shi, Qing; Yue, Tao; Nakajima, Masahiro; Takeuchi, Masaru; Huang, Qiang; Fukuda, Toshio
The 3D assembly of cellular structures is important for the fabrication of biological substitutes in tissue engineering. In particular, a micro-channel with a 200 μm diameter is of interest because of its promising ability to construct the vascular network for oxygen and nutrition delivery in thick biological substitutes in the future. In this paper, a novel rail-guided micro-robot-team system is proposed for the micro-assembly of a cellular structure. The cellular two-dimensional (2D) component was fabricated by ultraviolet (UV) illumination of a cross-linkable hydrogel. The modular rail-guided micro-robotic system was set up with multi-micromanipulators as the modules and controlled with hybrid motors to achieve an operation resolution of 30 nm. To realize the bottom-up fabrication of the cellular micro-channel, different micro-assembly strategies with multi-manipulators were developed. The micro-assembly success rate and the efficiency of the different strategies were evaluated based on the assembly of micro-donuts. Through the novel, designed, concentric movement of the multi-manipulators along the rail, arbitrary change of the approaching angle and the coordination posture was achieved to improve the micro-assembly's flexibility. The operation range for every micromanipulator in different coordinated manipulation modes was analysed to avoid the breakdown of the assembled 3D structure. The image processing for the target location and end-effector identification was conducted to improve assembly efficiency in the micro-robot-team system. Finally, the assembly of the cellular vascular-like micro-channel was achieved with coordinated manipulation in the rail-guided micro-robot-team system.